(untitled) (Research, Society and Development, 2025)
Objective: We assessed the level of user satisfaction with oral health services in two health facilities in Maputo city. Methodology: We conducted a cross-sectional study using systematic sampling. Data was collected using a pre-tested questionnaire and we evaluated satisfaction across four dimensions: accessibility, infrastructure, interaction and provision of care. We performed descriptive and bivariate analyses using the Chi-square. Results: Out of 294 selected users, 266 (90.5%) were included in the study. Among them, 66.5% were female, half were aged between 18 and 29 years and 74.8% had completed secondary education. The overall satisfaction level was 79.3%. Users reported the highest satisfaction with the interaction dimension (89.9%) and the lowest with accessibility (63.9%). They gave negative evaluations to service availability (15.1%), waiting area 36.5%), and equipment condition (31.6%). The Alto-Maé Health Center recorded a significantly higher satisfaction level (91.4%, p<0.001), compared to the Bagamoyo Health Center. We found no associations between overall satisfaction and socio-demographic variables. However, we observed associations with specific dimensions of satisfaction: age with accessibility (p≤0.021), education with infrastructure (p≤0.037), and occupation with both accessibility (p≤0.039) and interaction (p≤ 0.007). Conclusion: Users expressed a high level of satisfaction with oral health services in the two health facilities. Nevertheless, their concerns about service availability, waiting area and equipment highlight areas that require improvement.